2020
DOI: 10.3390/nu12030639
|View full text |Cite
|
Sign up to set email alerts
|

Food Reward and Food Choice. An Inquiry Through The Liking and Wanting Model

Abstract: What if consumers are getting obese because eating less calories is more difficult for persons that have a higher pleasure and desire towards food (Ikeda et al., 2005) and food companies do not help given only a two extreme option choice to satisfy their needs (i.e., low calories vs. high calories or healthy vs. unhealthy)? Reward systems are being described with a new conceptual approach where liking—the pleasure derived from eating a given food—and wanting—motivational value, desire, or craving—can be seen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 103 publications
1
13
1
Order By: Relevance
“…The results of this study highlight a significant but limited (mostly by one unit) improvement in quality of meals consumed by reduction in the consumption of calorie-dense fast food, fried food and SSBs. Contrary to our findings, some studies suggest that confinement increased intake of HFSS food items, which could be attributed to eating out of anxiety or boredom, a dip in motivation to maintain healthy eating or an increase in mood-driven eating [ 11 , 12 ]. However, in our study the participants reported less socializing and eating out, preference to home cooked meals, time availability for meal preparation, incorporation of immunity-boosting foods to maintain health and better family support in maintenance of healthy eating pattern as prime reasons for reduction in unhealthy eating behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study highlight a significant but limited (mostly by one unit) improvement in quality of meals consumed by reduction in the consumption of calorie-dense fast food, fried food and SSBs. Contrary to our findings, some studies suggest that confinement increased intake of HFSS food items, which could be attributed to eating out of anxiety or boredom, a dip in motivation to maintain healthy eating or an increase in mood-driven eating [ 11 , 12 ]. However, in our study the participants reported less socializing and eating out, preference to home cooked meals, time availability for meal preparation, incorporation of immunity-boosting foods to maintain health and better family support in maintenance of healthy eating pattern as prime reasons for reduction in unhealthy eating behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…Alas, half of the participants increased consumption of comfort foods, be them sweet or salty. Whether this is due to the induction of a vicious cycle is still a matter of debate, but there is a clear relation between anxiety levels and cravings/hunger pangs [20]. This agrees with very recent evidence showing that protein consumption is more stable than carbohydrate consumption, suggesting biological control mechanism(s) tightly regulate protein intake and, consequently, influence intake of other macronutrients and food constituents [21].…”
Section: Discussionsupporting
confidence: 80%
“…Before reaching the final output of food choice behavior, cognitive factors have their impacts on food decision-making. Possessing knowledge (especially nutritional and food-related knowledge) [ 24 , 34 , 48 , 52 , 56 , 57 , 58 , 64 , 70 , 78 , 79 , 82 , 88 , 93 , 94 , 97 , 106 , 107 ] as well as food management skills [ 41 , 48 , 52 , 75 , 83 , 90 , 92 , 97 ] can have great influence on food choice. For example, nutrition knowledge has been shown to be a partial mediator of the socio-demographic variation in food intake, especially for fruit and vegetables, implying that knowledge is an important factor in explaining variations in food choice [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…About the direction of influence among the factors in the conceptual models, fewer conceptual models are supported with empirical data [ 57 , 60 , 62 , 63 , 64 , 74 , 78 , 91 , 92 , 93 , 96 , 102 , 106 , 109 ].…”
Section: Discussionmentioning
confidence: 99%